2012
DOI: 10.1002/cam4.11
|View full text |Cite
|
Sign up to set email alerts
|

Soluble endothelial protein C receptor (sEPCR) is likely a biomarker of cancer‐associated hypercoagulability in human hematologic malignancies

Abstract: Elevated plasma level of soluble endothelial protein C receptor (sEPCR) may be an indicator of thrombotic risk. The present study aims to correlate leukemia-associated hypercoagulability to high level plasma sEPCR and proposes its measurement in routine clinical practice. EPCR expressions in leukemic cell lines were determined by flow cytometry, immunocytochemistry, and reverse transcription polymerase chain reaction (RT-PCR). EPCR gene sequence of a candidate cell line HL-60 was also determined. Plasma sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…In a previous study, we reported that malignant cells express and secrete EPCR and that sEPCR is associated with hypercoagulability in human hematological malignancies (10,11). We also reported that the EPCR gene sequence of HL-60 myeloblastic leukemia cells is quite identical to that of endothelial cells, in that it harbors the different SNPs (11) as previously reported for the endothelial cell gene (12).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…In a previous study, we reported that malignant cells express and secrete EPCR and that sEPCR is associated with hypercoagulability in human hematological malignancies (10,11). We also reported that the EPCR gene sequence of HL-60 myeloblastic leukemia cells is quite identical to that of endothelial cells, in that it harbors the different SNPs (11) as previously reported for the endothelial cell gene (12).…”
Section: Introductionsupporting
confidence: 58%
“…We previously reported that EPCR is expressed in human malignant blood cells, often resulting in higher plasma sEPCR levels (11). Using a retrospective clinical study (n=110), we observed that, when the plasma sEPCR level rises above the 200 ng/ml threshold, the risk of thrombosis also rises considerably (40%) in hematological pathologies (11).…”
Section: Discussionmentioning
confidence: 94%
“…There have been few studies investigating EPCR expression in hematological malignancies [36][37][38]. In these studies they detected EPCR expression in a wide range of malignant hematological cells.…”
Section: Discussionmentioning
confidence: 97%
“…As a substantial proportion of these patients (67%) had plasma sEPCR levels higher than controls, authors claimed that plasma sEPCR level may be a feasible marker which provides an illuminant insight into thrombotic risk assessment in patients wih hematological malignan cies. 5 Some reports have emphasized a reasonable relationship between sEPCR and TM levels and thrombotic complications. A total of 56 patients with central retinal vein occlusion (CRVO), 26 patients with branch RVO and 78 healthy subjects were enrolled in a study by Gumus et al Elevated levels of sEPCR were considered to be a risk factor for CRVO in this study.…”
Section: Discussionmentioning
confidence: 99%
“…3,[5][6][7] Although thrombohemorrhagic complications are considered as the most common causes of morbidity and mortality in MPNs, the etiology and pathogenesis of the clotting abnormalities still remain unclear. 3,[5][6][7] Clinical factors including age, previous history of thrombosis, obesity, hypertension and hyperlipidemia as well as elevated blood cell counts (leukocytosis, erythrocytosis and thrombocytoAssessment of Soluble Endothelial Protein C Receptor and Thrombomodulin Levels in Newly Diagnosed Myeloproliferative Neoplasms A AB BS S T TR RA AC CT T O Ob bj je ec ct ti iv ve e: : Thrombotic complications are considered as significant causes of morbidity and mortality in patients with myeloproliferative neoplasms (MPN). The protein C (PC) pathway plays a pivotal role in the regulation of the coagulation cascade through inactivation of factor Va and factor VIIIa, which is mediated by an intereaction between activated PC (APC) and endothelial PC receptor (EPCR).…”
mentioning
confidence: 99%